Seasonal variation of accelerations and decelerations by position in male basketball - Stoneman, B.; Olthof, S. B.; Burns, G. T.; Wong, A.; Zernicke, R. F. (International Journal of Sports Science & Coaching, 2025)
During basketball training and competition, players perform accelerations and decelerations, changes of direction, and jumps with little recovery. These movements place a range of loads on the players` bodies and vary across positions and over time. Limited research has quantified biomechanical loads longitudinally using game data and the ratio of accelerations to decelerations. This study investigated positional differences in accelerations, decelerations, and an acceleration-to-deceleration (AD) ratio in training and competition throughout a single season. Data from collegiate male basketball players (NCAA D-I) were collected with player tracking devices, Catapult Optimeye S5, for 30 games and 89 practices during the 2019-2020 season. Starting guards (n = 2), forwards (n = 3), and centers (n = 2) played more than 20 games and averaged more than 10 min/game. Significantly lower values occurred in practice vs. games for all metrics (p < .05). The biomechanical loads produced significantly different player-position profiles, and practice vs. game differences provided insights into AD ratio variations. Longitudinal changes revealed a significant decrease in the AD ratio and its day-to-day variation. These data provide a basis for assessing player performance, and future studies can extend the current analyses to examine performance changes between game segments and evaluate player performance changes at weekly levels across a season.